(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
The aim of the present study was to conduct phytochemical screening, perform acute oral toxicity effect and to evaluate the anti-inflammatory effect of ethanolic extracts of leaf and stem bark of Calophyllum inophyllum on albino Wistar rats. Carrageenan induced paw edema and cotton pellet granuloma techniques were applied to determine anti-inflammatory properties of the extracts. Extracts were administered orally. Acute oral toxicity studies were conducted using the OECD guidelines 423 Annexure – 2d. The results indicate the mortality was not observed during the toxicity studies and maximum safe does was determined. The anti-inflammatory effect of the extracts showed significant dose dependent effect (200 mg/kg b.w and 400 mg/kg b.w) on both acute and chronic models of inflammation i.e., carrageenan induced paw edema and cotton pellet granuloma respectively. Additionally, Calophyllum inophyllum leaves extract showed more activity compared to Calophyllum inophyllum stem bark extract.